2018
DOI: 10.1016/j.jpsychores.2017.11.001
|View full text |Cite
|
Sign up to set email alerts
|

Psychiatric comorbidities in patients with Atypical Odontalgia

Abstract: About half of AO patients had comorbid psychiatric disorders. Dental procedures are not necessarily causative factors of AO. In AO patients with comorbid psychiatric disorders, pain might have a larger emotional component than a sensory one. VAS, SDS, and SF-MPQ scores might aid in the noticing of underlying comorbid psychiatric disorders in AO patients.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
55
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 33 publications
(57 citation statements)
references
References 24 publications
2
55
0
Order By: Relevance
“…The most frequent kinds of non‐odontogenic toothache reported are myofascial pain, neuropathic pains of the trigeminal system and neurovascular pains . In addition, pain may originate from sinus problems, cardiac pathology, neoplasia and—rarely—secondary to a psychological disorder like schizophrenia . For each of these potential causes, this section will summarise diagnostic and pathophysiological characteristics, as well the suggested management approach.…”
Section: Non‐odontogenic Toothachementioning
confidence: 99%
See 1 more Smart Citation
“…The most frequent kinds of non‐odontogenic toothache reported are myofascial pain, neuropathic pains of the trigeminal system and neurovascular pains . In addition, pain may originate from sinus problems, cardiac pathology, neoplasia and—rarely—secondary to a psychological disorder like schizophrenia . For each of these potential causes, this section will summarise diagnostic and pathophysiological characteristics, as well the suggested management approach.…”
Section: Non‐odontogenic Toothachementioning
confidence: 99%
“…While the interaction between chronic pain and psychological factors has been widely accepted and documented in the framework of the biopsychosocial model, there is no evidence that psychological or emotional factors can induce tooth pain. Rarely, somatoform disorder or schizophrenia may be expressed as pain in teeth . In those patients, pain is present in multiple teeth with a sharp, stabbing and intense character.…”
Section: Non‐odontogenic Toothachementioning
confidence: 99%
“…Several studies reported that PDAP affects more women, with females being affected in 65%-86% of the cases (Klausner, 1994;Miura et al, 2018;Vickers, Cousins, Walker, & Chisholm, 1998).…”
Section: Female Predominancementioning
confidence: 99%
“…PDAP is frequently comorbid with TMD (Baad-Hansen, Leijon, Svensson, & List, 2008) and chronic tension-type headaches (TTH) (Baad-Hansen et al, 2008). Moreover, depression, somatization, other psychiatric conditions, and sleep disturbances have been reported in individuals with PDAP (Baad-Hansen et al, 2008;Ciaramella, Paroli, Lonia, Bosco, & Poli, 2013;Miura et al, 2018), who also present more jaw-related disability, worse psychosocial functioning, and lower quality of life when compared to controls (Durham, Exley, John, & Nixdorf, F I G U R E 1 Persistent dentoalveolar pain disorder characteristics in relation to those commonly reported with chronic overlapping pain conditions (adapted from Warren, 2014). Blue circles indicate met characteristics, while red circles represent unmet characteristics [Colour figure can be viewed at wileyonlinelibrary.com] 2013; Durham & Nixdorf, 2014;List et al, 2007;Shueb, Nixdorf, John, Alonso, & Durham, 2015).…”
mentioning
confidence: 99%
“…3 However, regardless of with or without psychiatric comorbidity, half of the patients with idiopathic oral pain (atypical odontalgia) still have their symptoms triggered by dental treatment. 4 This suggests an appropriate assessment of mental health before a dental procedure could help eliminate, but maybe not completely, the risk of developing various somatic symptoms, especially in patients with acute depression.…”
mentioning
confidence: 99%